2014
DOI: 10.7205/milmed-d-13-00336
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Age Differences in Growth Factor Concentrations From Platelet-Rich Plasma in Adults

Abstract: The use of platelet-rich plasma (PRP) to facilitate healing of orthopedic-related injuries has gained popularity; however, the clinical benefits are not consistent. Differences may result from variations in growth factor (GF) levels in normal populations. The purpose of this study was to determine if GF levels present in activated PRP preparations differed by gender and age (≤ 25 versus >25 years) in a healthy population (N = 102). All GFs analyzed (epidermal growth factor [EGF], hepatocyte growth factor [HGF]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 31 publications
9
69
2
1
Order By: Relevance
“…Batch‐to‐batch consistency in HPL batches seems to require the pooling of 40 to 50 PC donations, corresponding to approximately 250 donors when using “random‐donor” PCs. Pooling minimizes inherent donor‐to‐donor variability due to impact of age or sex, such as the content in growth factors and other cell growth–promoting molecules, which are important components for growth medium supplementation . However, pooling increases the risk of contamination by 1) window period donations, 2) viruses that are not tested for, or 3) emerging agents, making the implementation of virus/pathogen inactivation procedures required .…”
Section: Discussionmentioning
confidence: 99%
“…Batch‐to‐batch consistency in HPL batches seems to require the pooling of 40 to 50 PC donations, corresponding to approximately 250 donors when using “random‐donor” PCs. Pooling minimizes inherent donor‐to‐donor variability due to impact of age or sex, such as the content in growth factors and other cell growth–promoting molecules, which are important components for growth medium supplementation . However, pooling increases the risk of contamination by 1) window period donations, 2) viruses that are not tested for, or 3) emerging agents, making the implementation of virus/pathogen inactivation procedures required .…”
Section: Discussionmentioning
confidence: 99%
“…Further, estrogen and androgen facilitate angiogenesis through different mechanisms. Finally, females and males have different amounts of circulating pro-angiogenic and anti-angiogenic factors, which may further contribute to the sex differences in tumor angiogenesis epidermal growth factor (EGF), insulin growth factor-1 (IGF-1), PDGF-BB, and VEGF, were significantly higher in women [373]. Conversely, another study of plateletrich plasma found that PDGF-BB was higher in men and found no sex differences in IGF-1 levels [374].…”
Section: Sex Differences In Angiogenesismentioning
confidence: 99%
“…Such a relevant number of different preparation protocols should be taken into account whenever inconsistencies are found from comparing clinical outcomes reported in the literature [32]. The quality of PRP could be affected by patient's heterogeneity in terms of age, gender, body mass index, comorbidities, healing capabilities, and different lifestyles [33]. In order to reduce at least the protocol-dependent variability, the authors selected a closed preparation system, which, being automatic, limits the possibility of operator-dependent errors and reduces the risk of microbial contamination, while processing the blood.…”
Section: Introductionmentioning
confidence: 99%